Hubungan Pengetahuan Ibu Dan Dukungan Keluarga Dengan Pemberian Asi Eksklusif - Sari, Putri Dwi Novita; Khasanah, Nopi Nur; Wijayanti, Kurnia (Universitas Muhammadiyah Tangerang, 2024)
Exclusive breastfeeding is very important for babies aged 0-6 months, because it provides various benefits for both babies and mothers. For babies, breast milk increases immunity, meets nutritional needs, and has the potential to increase intelligence (IQ) and emotional intelligence (EQ). Meanwhile, for mothers, breast milk can reduce the risk of anemia, cancer, and postpartum hemorrhage. In addition, exclusive breastfeeding is also more economical, practical, and saves time. Various factors can influence the success of exclusive breastfeeding, including the level of maternal knowledge and family support. Therefore, the purpose of this study was to determine the relationship between maternal knowledge and family support with exclusive breastfeeding. Method: This study was quantitative research with a cross-sectional approach, and data collection was carried out through a questionnaire. The number of respondents in this study was 66 people, using the total sampling technique. The collected data were tested using Fisher's exact test. Results: Based on the analysis, it was found that out of 66 respondents, the majority had a high school education background, which was 59.1%, and most worked as housewives (IRT), totaling 90.9%. The research results also revealed that 93.3% of respondents had good knowledge, 77.3% received support from their families, and 92.4% provided exclusive breastfeeding to their babies. Conclusion: There is a significant relationship between maternal knowledge and exclusive breastfeeding, obtained a p value of 0.001 and there is a relationship between family support and exclusive breastfeeding, obtained a p value of 0.008.